2010
DOI: 10.1002/da.20761
|View full text |Cite
|
Sign up to set email alerts
|

Family income and youths' symptoms of depression and anxiety: a longitudinal study of the French GAZEL Youth cohort

Abstract: Clinicians need to be aware that youths growing up in low-income families in the community may be at risk of depression and anxiety during the period of transition to adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 51 publications
6
48
1
1
Order By: Relevance
“…For example, persistent socioeconomic disadvantage during early childhood has been found to be linked to poorer cognitive and behavioural outcomes in the early years (Dickerson and Popli 2016;Holmes and Kiernan 2013;Schoon et al 2010;Washbrook 2010). These findings also extend into middle childhood (McLeod and Shanahan 1996) and into early adolescence (Melchior et al 2010;Najman et al 2010;Strohschein 2005). Improvements in socioeconomic status have also been found to be related to better child mental health outcomes (Costello et al 2003).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…For example, persistent socioeconomic disadvantage during early childhood has been found to be linked to poorer cognitive and behavioural outcomes in the early years (Dickerson and Popli 2016;Holmes and Kiernan 2013;Schoon et al 2010;Washbrook 2010). These findings also extend into middle childhood (McLeod and Shanahan 1996) and into early adolescence (Melchior et al 2010;Najman et al 2010;Strohschein 2005). Improvements in socioeconomic status have also been found to be related to better child mental health outcomes (Costello et al 2003).…”
Section: Introductionmentioning
confidence: 71%
“…This is an important conclusion. Prior research has tended only to utilise cross-sectional data and there has been a gap in evidence about whether early childhood factors, including cumulative adversities, can help to explain the variations that exist in children's subjective well-being in the way that they have done for educational outcomes (Caro et al 2009;Crawford et al 2015;Washbrook 2010) and mental health problems (Melchior et al 2010;Najman et al 2010;Strohschein 2005). While there are limitations to the current analysis (discussed below) this broad finding suggests that how children feel about their lives may be better understood by contemporaneous factors than historical ones.…”
Section: Key Messages and Implicationsmentioning
confidence: 99%
“…Parental household income was reported by parents in the 1989 GAZEL study questionnaire and dichotomized at the median value, equivalent to the average household income in France at the time (EUR ≤1,981 vs. ≥1,981 per month) [38,39]. …”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies highlight the relationship between attachment difficulties and the family's economic problems. Melchior et al (2010) have reported child and adolescent psychological disorders in families whose financial difficulties persist and aggravate over time in a French community. Secure attachment is less easily implemented when attentive and responsive parenting is influenced negatively by stressful factors related to low income than when the families have a better socio-economic status.…”
Section: Introductionmentioning
confidence: 99%